2023
DOI: 10.3390/en16217356
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Emission Prediction and the Reduction Pathway in Industrial Parks: A Scenario Analysis Based on the Integration of the LEAP Model with LMDI Decomposition

Dawei Feng,
Wenchao Xu,
Xinyu Gao
et al.

Abstract: Global climate change imposes significant challenges on the ecological environment and human sustainability. Industrial parks, in line with the national climate change mitigation strategy, are key targets for low-carbon revolution within the industrial sector. To predict the carbon emission of industrial parks and formulate the strategic path of emission reduction, this paper amalgamates the benefits of the “top-down” and “bottom-up” prediction methodologies, incorporating the logarithmic mean divisia index (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Feng et al utilized a combination of LMDI and LEAP models to forecast the carbon emissions of industrial park groups within an economic development zone in Yancheng, spanning from 2020 to 2035, under both baseline and low-carbon scenarios. The findings indicate that the third scenario, as per the low-carbon scenario, is deemed most suitable for park development [18]. Zeng et al [19] conducted a study on different peaking scenarios and found that the Yangtze River Delta urban agglomeration, as a whole, is capable of achieving carbon peaking on time under three simulation paths.…”
Section: Application Of the Stirpat Model In Predicting Carbon Emissionsmentioning
confidence: 99%
“…Feng et al utilized a combination of LMDI and LEAP models to forecast the carbon emissions of industrial park groups within an economic development zone in Yancheng, spanning from 2020 to 2035, under both baseline and low-carbon scenarios. The findings indicate that the third scenario, as per the low-carbon scenario, is deemed most suitable for park development [18]. Zeng et al [19] conducted a study on different peaking scenarios and found that the Yangtze River Delta urban agglomeration, as a whole, is capable of achieving carbon peaking on time under three simulation paths.…”
Section: Application Of the Stirpat Model In Predicting Carbon Emissionsmentioning
confidence: 99%
“…Environmental pollution and energy security have become global challenges and pose serious threats to human survival and development [3,4]. A global consensus is emerging in support of the promotion of green energy economics and the expedited transition to a low-carbon future [5,6]. The Integrated Energy System (IES) stands as a key enabler in this paradigm, seamlessly interconnecting a diverse array of energy sources, encompassing renewables, thermal energy, and natural gas [7].…”
Section: Introductionmentioning
confidence: 99%